Improvement in treatment of soak liquor by combining electro-oxidation and biodegradation. Issue 53 (13th May 2016) - Rajeswari, S.; Vidhya, S.; Sundarapandiyan, S.; Saravanan, P.; Ponmariappan, S.; Vidya, K.
Abstract : A combined process involving electro-oxidation and biodegradation by halophilic bacteria was applied to treat wastewater effectively for discharge. Abstract : Soak liquor generated from the leather processing industry contains high organic load, making it a challenge to treat it efficiently. A combined process involving electro-oxidation and biodegradation by halophilic bacteria was applied to treat wastewater effectively for discharge. Electrolysis was performed prior to biological treatment in an electrochemical reactor at a current density of 0.012 A cm −2 for a period of 30 minutes. Titanium Substrate Insoluble Anode (TSIA) was used as an anode and titanium mesh was used as a cathode. Biological degradation was carried out with two isolated microbial strains at pH 6. The combination of electro-oxidation and biodegradation was recorded as a good technique in terms of COD (Chemical Oxygen Demand), BOD (Biological Oxygen Demand) and TKN (Total Kjeldahl Nitrogen) removal efficiency with values of 95%, 85%, and 88% respectively. The present study claims that the integrated process gives better performance for the reduction of COD when compared to previous studies.